(De)Coding of Abbreviations from the Last Two Decades - Teodora Ilieva (Педагогически форум)
The publication examines abbreviations and combinations with an abbreviated element registered in the public domain in the last two decades, as well as the re-actualization of long-known abbreviations. The system analysis unfolds in several aspects: structural (mono-, bi- and polyelement, cut off abbreviations), temporal (neo-abbreviations and renewal of already known abbreviations, renomination), etymological (Bulgarian – regional and national, loan words, international abbreviations), functional (with distribution in written and/or usual utterances), stylistic (neutral, stylized, occasionally transposed, result of language play). The two main approaches that are advanced and woven into the analysis of the above-mentioned groups are the coding of significant nominations by means of various types of abbreviations and the connotative decoding (desabbreviation) of part of the abbreviation formations. In the study, cases of syngraphy, abbreviated homonymy and synonymy, archaization, competition between acronyms, which are registered in modern language practice, are marked.